Some engineering aspects of nature conservation measures to enhance small hydropower - Hayrapetyan, V. G.; Gabayan, G. S.; Tokmajyan, H. V.
The last decade can be considered as the decade of small power engineering development. High activity in this business has affected practically all large and small rivers of Armenia. In this situation, the investors face various well-grounded, and often groundless environmental problems. Some of these problems are considered on the basis of summarizing the experience of construction and operation of some small scale hydropower plants of the country, gained by carrying out studies on more than 60 power stations. Последнее десятилетие можно считать десятилетием развития малой энергетики. Высокая активность в этом бизнесе затронула практически все большие и малые реки Армении. В этой ситуации перед инвесторами возникают различные обоснованные, а часто необоснованные экологические проблемы. Рассматриваются некоторые из них на основании обобщения опыта строительства и эксплуатации некоторых малых ГЭС республики, изученного на более чем 60 станциях.
Keywords: Water systems